2014
DOI: 10.1139/cjpp-2014-0092
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor alpha protects heart cultures against hypoxic damage via activation of PKA and phospholamban to prevent calcium overload

Abstract: This study aims to elucidate the mechanisms by which tumor necrosis factor alpha (TNFα) provides protection from hypoxic damage to neonatal rat cardiomyocyte cultures. We show that when intracellular Ca(2+) ([Ca(2+)]i) levels are elevated by extracellular Ca(2+) ([Ca(2+)]o) or by hypoxia, then TNFα decreased [Ca(2+)]i in individual cardiomyocytes. However, TNFα did not reduce [Ca(2+)]i after its increase by thapsigargin, (a SERCA2a inhibitor), indicating that TNFα attenuates Ca(2+) overload through Ca(2+) upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Kurrelmeyer et al reported the importance of TNF signaling in protecting cardiomyocytes against ischemic injury [29]. The protective mechanism against hypoxic damage could be via activation of protein kinase A which stimulates SERCA2a thereby reducing intracellular calcium concentration during calcium overload [30]. Thus, TNF-α signaling helps in pumping calcium ions in the sarcoplasmic reticulum and restoring cytosolic calcium back to baseline levels [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kurrelmeyer et al reported the importance of TNF signaling in protecting cardiomyocytes against ischemic injury [29]. The protective mechanism against hypoxic damage could be via activation of protein kinase A which stimulates SERCA2a thereby reducing intracellular calcium concentration during calcium overload [30]. Thus, TNF-α signaling helps in pumping calcium ions in the sarcoplasmic reticulum and restoring cytosolic calcium back to baseline levels [30].…”
Section: Discussionmentioning
confidence: 99%
“…The protective mechanism against hypoxic damage could be via activation of protein kinase A which stimulates SERCA2a thereby reducing intracellular calcium concentration during calcium overload [30]. Thus, TNF-α signaling helps in pumping calcium ions in the sarcoplasmic reticulum and restoring cytosolic calcium back to baseline levels [30]. It is possible that the reduction of TNF-α levels due to GBE observed in the present study may be as a consequence of: (a) reduced expression of the TNF-α gene and a lessened production of TNF-α protein, or, (b) increased production of soluble TNF-α receptors, which could bind and inactivate TNF-α [31].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that prolonged TNF-α blockade may suppress ROS generation below the threshold which is required for physiological regulation of the Keap1/Nrf2 pathway. In support of this concept recent studies suggest that basal levels of TNF-α may have beneficial effects in acute heart ischemia [33] , [34] .…”
Section: Introductionmentioning
confidence: 93%